1995
DOI: 10.1002/pssb.2221870108
|View full text |Cite
|
Sign up to set email alerts
|

Photoionization of Shallow Donor Impurities in Finite‐Barrier Quantum Wells

Abstract: The dependence of the photoionization cross-section on photon energy is calculated for shallow donors in finite-barrier GaAs/Ga, -,AI,As quantum wells as well as the binding energy as a function of well width. The effect of a magnetic field is also considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…The same work as before has been done for light polarized in the z-direction by considering optical transitions that take place from the impurity ground state as the initial state to the second subband as the final continuum state [55]. Moreover, the spectral dependence of the photoionization cross-section on photon energy for shallow donor impurities in a finitebarrier quantum well and for incident light polarized along the z-axis of the well has been studied [56]. More recently, the excitation energy dependence of the photoionization cross-section of a hydrogenic donor impurity in an infinite-barrier CdTe quantum well as a function of the well width, taking into account the interaction between electron and bulk longitudinal-optical phonons has been studied [57].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The same work as before has been done for light polarized in the z-direction by considering optical transitions that take place from the impurity ground state as the initial state to the second subband as the final continuum state [55]. Moreover, the spectral dependence of the photoionization cross-section on photon energy for shallow donor impurities in a finitebarrier quantum well and for incident light polarized along the z-axis of the well has been studied [56]. More recently, the excitation energy dependence of the photoionization cross-section of a hydrogenic donor impurity in an infinite-barrier CdTe quantum well as a function of the well width, taking into account the interaction between electron and bulk longitudinal-optical phonons has been studied [57].…”
Section: Introductionmentioning
confidence: 98%
“…The photon energy dependence of the photoionization cross-section in low-dimensional electronic systems is generally determined by the impurity ground state wavefunction, the potential which links the electron to the donor impurity and the conduction subband of the host crystal and by the wavefunction of the conduction subbands into which the charge carrier is excited. Recently, much attention has been devoted to the study of the hydrogenic impurity photoionization cross-section in systems with reduced dimensionality such as quantum wells [53][54][55][56][57][58] and quantum-well wires [59][60][61]. Most of these works can be summarized as follows: Takikawa et al [53] have experimentally and theoretically examined the photoionization of the deep traps in AlGaAs/GaAs multiple quantum well layers grown by metalorganic chemical vapour deposition.…”
Section: Introductionmentioning
confidence: 99%
“…They found out that the photoionization cross-section depended upon the polarization of the incident light relative to the direction of the carrier confinement. Ilaiwi and El-Said [5] extended these calculations using the finite barrier model. They found out that the photoionization cross-section depended upon the polarization of the incident light relative to the direction of the carrier confinement.…”
Section: Introductionmentioning
confidence: 98%
“…Lax [1] first investigated the photoionization cross-section of hydrogenic impurities in bulk semiconductors. In recent years, work has been done on the photoionization crosssection of hydrogenic impurities in dimensionally reduced structures such as quantum wells, wires and quantum dots [2][3][4][5][6][7][8][9][10]. It has been found that greater the confinement in such low-dimensional structures, greater the binding energy of these hydrogenic impurities.…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge of the effect of the confining potential barriers on the photoionization and the binding energy of impurities is important, since the optical and transport properties of semiconductor materials are strongly influenced by both doping impurities and the shape of the confining potentials of low dimensional systems. Therefore, several works have investigated the photoionization cross-section of hydrogenic impurities as a function of the photon energy in structures of reduced dimensionally such as quantum wells (QWs), wires (QWWs) and quantum dots (QDs) [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%